Hoy! Tsinoy ako! an ethnographic analysis of the representation of the Tsinoy in Philippine television - Sy, Stanly Galo Claudio 1990- (2012)
"This study seeks to analyze the politics of the representation of young Tsinoys in Philippine television. This will be framed using an ethnographic inquiry based on the incongruence of my experiences growing up as a Tsinoy vis-a-vis the portrayal of young Tsinoys in Philippine television. George Herbert Mead's Symbolic Interactionism will be used as the framework for this study, particularly his discourse on how needs of certain groups are identified by their experiences. There is also a brief discussion on the concept of one's identity based on nation. Edward Said's Orientalism will be used as the concepts of othering and exoticization are useful in the analysis of representation. This thesis employs textual analysis of the television series My Binondo Girl as a text. The study also uses ethnography through a personal narrative of my construction of my identity as a Tsinoy. Therefore, I will undertake this study as phenomenological project i.e.,both as a researcher and as a subject."